Control biologico de araña roja (tetranychus urticae), en tres variedades de rosas (rosa sp) de exportacion a traves de dos depredadores biologicos en la empresa Texas Flowers S.A. Cotopaxi - Lema Toapanta, Silvia Margoth (2013)
In the present investigation raised the topic called " Biological control of spider mites ( Tetranychus urticae ) in three varieties of roses ( Rosa sp ) export through two biological predators Texas Flowers SA company Cotopaxi " , the study was conducted at the Texas company located in the parish Flowers Tanicuchi. The overall objective was to evaluate the biological control of spider mites ( Tetranychus urticae ) in three varieties of roses ( Rosa sp ) export through two biological predators Texas Flowers SA company Cotopaxi . The specific objectives were to determine which predator is in control of how best release different frequencies . Evaluate what variety responsive to biological control in the management of spider mites ( Tetranychus urticae ) and Perform economic analysis of each treatment. The variables studied were : Percentage of effectiveness of biological predators , stem length , bud length , bud diameter and the thickness of the stem.